SAT0326 Efficacy and Safety of Autologous Platelet Lysate Eye Drops in Sjögren's Syndrome: A New Approach. (15th July 2016) - Parisi, S.; Aragno, V.; Testa, V.; Scarati, M.; Priora, M.; Machetta, F.; Peroni, C.L.; D'Antico, S.; Fusaro, E.; Caporali, R.; Montecucco, C.
Abstract : Background: Sjögren's Sydrome (SS) is a chronic multisystem autoimmune disease characterized by hypofunction of salivary and lacrimal glands. The result of the immune-mediate infiltration of the lacrimal gland is a severe dry eye disease. None of the commercially available artificial tear preparations and anti-inflammatory topical treatment has the properties of the human tears as Growth factors (GFs), that are necessary for maintenance of normal corneal epithelium. Platelet alfa granules are a major source of GFs and are rich in platelet derived growth factor (PDGF), which plays an important role in the maintenance of ocular surface and tear film stability (1). Objectives: To determine the efficacy and safety of autologous platelet lysate (APL) eye drops in patients with primary SS dry eye, refractory to standard therapy, in comparison to patients treated with artificial tears. We focused on the effect of APL on cornea morphology with the in vivo confocal microscopy (IVCM). Methods: We included patients with a diagnosis of SS according to the classification criteria of the American-European Consensus (2), a dry eye severity level ≥2 (Dry Eye Severity Grading Scheme, Workshop 2007). Patients were assigned in two groups, according to the randomization criteria 1:1 – Group A used autologous platelet lysate (BiomedDevice) QID for 90 days. – Group B used preservative-free artificial tears QID (Ialuronic Acid 0, 2%) for 90 days. Ophthalmological assessments included: ocular surface disease index (OSDI), Schirmer test, fluoresceine score and break up time (BUT). Both Group A and Group B underwent IVCM; corneal basal epithelium, sub basal nerves, Langherans cells, anterior stroma activated keratocytes were evaluated. The study was conducted in accordance with the Declaration of Helsinki (1964) and approved by our Ethics Committee. Results: 43 patients (female:male =42:43) with mean age of 59, 75 years (SD±13, 10) affected by primary SS from 7, 48 years (SD±5, 56) were enrolled. The two groups (A=22 pts; B=21 pts) did not have significant differences at baseline in terms of disease (duration, autoantibodies) and treatment (steroids, DMARDs) characteristics. In group A, the mean of improvement of OSDI, fluorescein score and BUT values (Δ38.82; Δ1.0; Δ1.5 respectively) were higher than group B (Δ7.07; Δ0.0; Δ0.0 respectively) with statistical significance (p<0.05). The IVCM showed a significant increase in basal epithelium cells density, sub basal nerve plexus density and number and a decrease in Langerhans cells density (p<0.05) only in group A. No adverse events were observed in all patients treated. Conclusions: APL has proved to be effective and safety in the treatment of SS dry eye and IVCM seems to be a useful tool to visualize cornea morphologic modifications. Further studies are required to evaluate the long-term effects and the timing of retreatment. References: Pezzotta S, Del Fante C, Scudeller L et al. Autologous platelet lysate for treatment of refractory ocular GVHD. Bone Marrow Transplantation 2012; 47, 1558–1563. Vitali C, Bombardieri S, Jonsson R, et al. Classification criteria for Sjogren's syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. Ann Rheum Dis. 2002; 61:554–8. Disclosure of Interest: None declared